2017
DOI: 10.3390/s17092072
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Neighborhood-Scale Spatial Variations of Ozone at Open Space and Urban Sites in Boulder, Colorado Using Low-Cost Sensor Technology

Abstract: Recent advances in air pollution sensors have led to a new wave of low-cost measurement systems that can be deployed in dense networks to capture small-scale spatio-temporal variations in ozone, a pollutant known to cause negative human health impacts. This study deployed a network of seven low-cost ozone metal oxide sensor systems (UPods) in both an open space and an urban location in Boulder, Colorado during June and July of 2015, to quantify ozone variations on spatial scales ranging from 12 m between UPods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…The correlation observed between Atmos and reference instruments for measured PM 2.5 was better than that for PM 10 (Supplementary Figure S3). Some of the recent papers from other countries have also shown that low-cost sensors' PM 2.5 matches more in comparison to PM 10 [8]. In the case of PM 2.5 as well, we observed p < 0.001 for all four cases.…”
Section: Distribution Pattern and Pairwise Correlation Of Measured Pmsupporting
confidence: 78%
“…The correlation observed between Atmos and reference instruments for measured PM 2.5 was better than that for PM 10 (Supplementary Figure S3). Some of the recent papers from other countries have also shown that low-cost sensors' PM 2.5 matches more in comparison to PM 10 [8]. In the case of PM 2.5 as well, we observed p < 0.001 for all four cases.…”
Section: Distribution Pattern and Pairwise Correlation Of Measured Pmsupporting
confidence: 78%
“…In another example, researchers demonstrated the feasibility of collecting personal CO, NO 2 , O 3 , and CO 2 exposure data with uncertainty estimations using a portable, wearable system (Piedrahita et al, 2014). Several studies have also made use of sensors to study the spatial variability of O 3 on various scales (Sadighi et al, 2018;Cheadle et al, 2017;Moltchanov et al, 2015). Connected to this effort on sensor applications, there has been much work evaluating the performance of individual sensors (Masson et al, 2015a, b;Spinelle et al, 2015Spinelle et al, , 2017Lewis at al., 2016) and demonstrating the performance of different calibration approaches (Zimmerman et al, 2018;Kim et al, 2018;Cross et al, 2017).…”
Section: Previous Sensor Researchmentioning
confidence: 99%
“…All data are logged to an onboard micro-SD card. As configured, these pods draw roughly 11 W. These systems have been used in several other indoor and outdoor air quality studies (Casey et al, 2018;Sadighi et al, 2018;Cheadle et al, 2017). Figure 1 includes a labeled photo of a Y-Pod interior and a photo of two Y-Pods deployed.…”
Section: Instrumentation -Low-cost Sensor Systemsmentioning
confidence: 99%
“…As configured, these Pods draw roughly 11 Watts. These systems have been used in several other indoor and outdoor air quality studies (Casey et al, 2017;Sadighi et al, 2017, Cheadle et al, 2017. …”
Section: Instrumentation -Low-cost Sensor Systemsmentioning
confidence: 99%
“…estimations using a portable, wearable system (Piedrahita et al, 2014). Several studies have also made use of sensors to study the spatial variability of O3 on various scales Cheadle et al, 2017;Moltchanov et al, 2015).…”
Section: A Place For Sensorsmentioning
confidence: 99%